Global Patterns of QALY and DALY Use in Surgical Cost-Utility Analyses: A Systematic Review. - Arturo J Rios-Diaz; Jimmy Lam; Margarita S Ramos; Andrea V Moscoso; Patrick Vaughn; Cheryl K Zogg; Edward J Caterson (PLoS ONE)
Background Surgical interventions are being increasingly recognized as cost-effective global priorities, the utility of which are frequently measured using either quality-adjusted (QALY) or disability-adjusted (DALY) life years. The objectives of this study were to: (1) identify surgical cost-effectiveness studies that utilized a formulation of the QALY or DALY as a summary measure, (2) report on global patterns of QALY and DALY use in surgery and the income characteristics of the countries and/or regions involved, and (3) assess for possible associations between national/regional-income levels and the relative prominence of either measure. Study design PRISMA-guided systematic review of surgical cost-effectiveness studies indexed in PubMed or EMBASE prior to December 15, 2014, that used the DALY and/or QALY as a summary measure. National locations were used to classify publications based on the 2014 World Bank income stratification scheme into: low-, lower-middle-, upper-middle-, or high-income countries. Differences in QALY/DALY use were considered by income level as well as for differences in geographic location and year using descriptive statistics (two-sided Chi-squared tests, Fischer's exact tests in cell counts <5). Results A total of 540 publications from 128 countries met inclusion criteria, representing 825 "national studies" (regional publications included data from multiple countries). Data for 69.0% (569/825) were reported using QALYs (2.1% low-, 1.2% lower-middle-, 4.4% upper-middle-, and 92.3% high-income countries), compared to 31.0% (256/825) reported using DALYs (46.9% low-, 31.6% lower-middle-, 16.8% upper-middle-, and 4.7% high-income countries) (p<0.001). Studies from the US and the UK dominated the total number of QALY studies (49.9%) and were themselves almost exclusively QALY-based. DALY use, in contrast, was the most common in Africa and Asia. While prominent published use of QALYs (1990s) in surgical cost-effectiveness studies began approximately 10 years earlier than DALYs (2000s), the use of both measures continues to increase. Conclusion As global prioritization of surgical interventions gains prominence, it will be important to consider the comparative implications of summary measure use. The results of this study demonstrate significant income- and geographic-based differences in the preferential utilization of the QALY and DALY for surgical cost-effectiveness studies. Such regional variation holds important implications for efforts to interpret and utilize global health policy research. PROSPERO registration number: CRD42015015991.